1.1 SOCIAL MEDIA MARKETING RETAINS BRAND EQUITY DURING PRODUCT CRISIS - Zafar, Fareeha; Javaid, Kinza; Amin, Hafsa; Hammad, Ahmad (Advances in Social Sciences Research Journal, 2017)
The main objective of this study is to explore how social media marketing help brands when brands facings crises. Brand equity is a priceless asset of companies. Most of owners of different businesses say that use of social media do miracles for their businesses. Social media consists of online web interactive tools such as Facebook, YouTube, Google plus, Twitter, Snap chat, Blogs, WhatsApp Etc. Through these tools companies interact with their customers to maintain positive relations with them and to become more close to customers. To support our research we use case study of Maggi Noodles brand in India. In order to accomplish the objective of the study we use Brand Asset Valuator model. The findings of our research shows that social media has positive effect on brand equity during crisis. We also find that where the social media services are not available there are less chances of brand improvement and it has negative effects on brand loyalty and brand equity.